Evaluation of Surface Hygiene of the Surrounding Objects in a University Hospital - Daiva Petruševičienė; Zita Gierasimovič; Greta Gailienė; Eglė Lendraitienė; Sigitas Mingaila (Lithuanian Sports University, 2020)
Research background. Hygiene of the surfaces means a clean environment of a hospital, especially that of a patient, which consists of constant basic cleaning and disinfection. The registration, analysis and storage of data on cleaning, disinfecting the surrounding objects is a successful stage in ensuring clean surfaces. The registration of documents and the cleaning and disinfecting schedule help to determine the tender spots in the surface cleaning. It makes easy to establish the surface hygiene violations, participation of the nursing and auxiliary staff in disinfecting the surfaces, problems related to the surface disinfection, and make the analysis of the mistakes made easier. The aim of the study. To assess a 2009-2011 hygienic preparation of medical surfaces, which have an effect on the transmission of the hospital-acquired infection, and the efficiency of the preventative measures. Methods. The survey was conducted in university hospital in 2009-2011. To evaluate the surface hygiene of the environmental objects the test of the remains of biological contamination was chosen using the chemical means HemoCheck-S™. The accuracy of the test is 0.1 µq of the remains of biological contamination on the surfaces under investigation. The results are evaluated by calculating the amount of denatured biological contamination from the highest concentration to 0. The surface contamination is evaluated in points from "0" to "5", where "0" is no contamination (medical surface is fully prepared for a procedure), and "5" is maximum contamination (100 µq, maximum contamination shown by the HemoCheck-S™ test). Results. Investigation shows that the surfaces belonging to the low-risk group are contaminated most heavily. The analysis of the investigations carried out during three years leads us to the conclusion that during the time of cleaning the surface, the staff fails to observe the sequence and do not change soft inventory (napkins) intended for cleaning. This is testified by presence of biological contamination in the low-risk group: switch-boards on the patients' beds, cupboards and drip mounts. Conclusions. Insufficient hygiene of high, medium risk and often touched surfaces and surfaces of nursing measures was established. The inadequate preparation of the medical surfaces was most often made in the Intensive Care Intensive Therapy units. Keywords: hygienic preparation; medical surfaces; the hospital-acquired infection.